2014
DOI: 10.1021/np500556t
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal Alkaloids from the Marine Sponge Corticium niger That Inhibit Growth of Human Colon Carcinoma Cells

Abstract: Bioinformatic analysis of data from the NCI-60 cell cytotoxicity screen revealed a subset of extracts that showed selective cytotoxic activity toward human colon carcinoma cell lines. Bioassay-guided fractionation of a colon cancer selective extract from a Philippines collection of the marine sponge Corticium niger provided two new steroidal alkaloids, plakinamines N (1) and O (2), along with two known compounds of the plakinamine class (3, 4). The structures of these compounds were elucidated by interpretatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Natural and natural-related compounds are the most commonly used drugs worldwide; hence, the first anticancer agents with a steroid structure were of herbal origin [49][50][51][52][53][54][55]. Besides natural plant steroids, some endogenous steroid metabolites are also reported to be potent antiproliferative agents [10][11][12][13][14][15][16]56].…”
Section: Discussionmentioning
confidence: 99%
“…Natural and natural-related compounds are the most commonly used drugs worldwide; hence, the first anticancer agents with a steroid structure were of herbal origin [49][50][51][52][53][54][55]. Besides natural plant steroids, some endogenous steroid metabolites are also reported to be potent antiproliferative agents [10][11][12][13][14][15][16]56].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of two dimethylamino groups in 1 was suggested by the resonances observed as two broadened singlets (δ H 2.84 and δ H 2.85) integrating for 12 protons attached to carbon resonances observed at δ C 42.7 and 40.5. A literature search suggested that similar resonances are found in the plakinamine class of natural products [5][6][7][8][9][10][11][12][13][14][15] and comparison of the NMR data to the published data suggested that 1 is most similar to plakinamines L and M [14,15]. Other characteristic resonances observed in the 1 H NMR spectrum of 1 were the methyl resonances observed at δ H 0.59 (H 3 -18, s) and δ H 0.86 (H 3 -19, s), which are consistent with the angular methyl groups of a steroidal alkaloid.…”
Section: Chemical Analysismentioning
confidence: 89%
“…Different classes of marine alkaloids, such as plakinamine and fascaplysin, have been described in the literature with similar in vitro cytotoxic effects . However, few studies have demonstrated the cytotoxic effects of marine alkaloids against breast cancer cell lines .…”
Section: Discussionmentioning
confidence: 99%